Inflammatory skin disease in transgenic mice that express high levels of interleukin 1 alpha in basal epidermis. - Groves, R W (1995)
Resting epidermal keratinocytes contain large amounts of interleukin 1 (IL-1), but the function of this cytokine in the skin remains unclear. To further define the role of IL-1 in cutaneous biology, we have generated two lines of transgenic mice (TgIL-1.1 and TgIL-1.2) which overexpress IL-1 alpha in basal keratinocytes. There was high-level tissue-specific expression of transgene mRNA and protein and large quantities of IL-1 alpha were liberated into the circulation from epidermis in both lines. TgIL-1.1 mice, which had the highest level of transgene expression, developed a spontaneous skin disease characterized by hair loss, scaling, and focal inflammatory skin lesions. Histologically, nonlesional skin of these animals was characterized by hyperkeratosis and a dermal mononuclear cell infiltrate of macrophage/monocyte lineage. Inflammatory lesions were marked by a mixed cellular infiltrate, acanthosis, and, in some cases, parakeratosis. These findings confirm the concept of IL-1 as a primary cytokine, release of which is able to initiate and localize an inflammatory reaction. Furthermore, these mice provide the first definitive evidence that inflammatory mediators can be released from the epidermis to enter the systemic circulation and thereby influence, in a paracrine or endocrine fashion, a wide variety of other cell types.